The great Muppet caper [videorecording (DVD)] - Grade, Lew, 1906-1998; Raposo, Joe; Patchett, Tom; Cleese, John; Morley, Robert; Goelz, Dave; Nelson, Jerry, 1934-2012; Morris, Oswald, 1915-2014; Kemplen, Ralph, 1912-2004; Henson, Jim; Grodin, Charles; Rigg, Diana; et al. (Disney DVD., 2005)
Kermit, Fozzie Bear, and Gonzo are reporters who travel to London to follow up on a jewel heist.